Biomimetic porous polypropylene foams with special wettability properties - Huang, Pengke; Wu, Fei; Shen, Bin; Zheng, Hao; Ren, Qian; Luo, Haibin; Zheng, Wenge (Composites. Part B, Engineering, 2020)
Nowadays, the subject of wettability still has received little attention in the scientific literature, especially in the cellular solids, despite its significant role in the pervasiveness of the water treatment. Herein, inspired by the mussel, a green method was developed to construct nano-/micro-structures on the multi-structural polypropylene (like the dense solids, big hollow, small hollow and hierarchical open/closed-cell porous structure) by the surface-adherent polydopamine. Moreover, the relationship between both surface chemical and physical (such as pore structure and size) properties of the porous media, and wettability were studied. Besides, water–glycerol mixture solutions with various viscosities were used to study the spreading and imbibition behavior in the porous polypropylene foams, and the surface free energy of the different cellular solids (before and after modification) was estimated by Owens-Wendt equation. More interestingly, different kinds of the super-wetting materials like super-amphiphilic and hierarchical super-hydrophilic/super-hydrophobic, etc., were successful prepared. Both fundamental theoretical and numerical analysis were also conducted to reveal the mechanism of the penetration or surface repellency toward a drop, and to predict the transport of fluids in porous media. We believe that this work may serve as a source of inspiration in designing other advanced functional materials. [Display omitted]